(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the factors that influence the development of linguocultural units in the context of globalization. It examines the interaction between language and culture, as well as the role of linguoculturemes in shaping identity and facilitating intercultural communication. The article analyzes the processes of adaptation and the functioning of linguoculturemes in various discourses, including political, literary, and online communication. Furthermore, it investigtes the relationship between history, social environment, and the evolution of linguocultural elements.